ANALISIS LAJU PENDINGINAN DAN KONSUMSI ENERGI LISTRIK PADA MESIN PENDINGIN LUCAS NULLE TYPE RCC2 MENGGUNAKAN REFRIGERAN R-600A - Gredio Lewu; Frans Palobo Sappu; Hengky Luntungan (JURNAL POROS TEKNIK MESIN UNSRAT, 2021)
Refrigeration machines already play an important role in the lives of modern society. In order for a cooling machine to be utilized optimally, the cooling capacity of the cooling machine must be in accordance with the heat load and electrical energy consumption it overcomes. This research aims to find out the performance of cooling engines in terms of cooling rate and electrical energy consumption when using R-600a refrigerant in Lucas Nulle type RCC2 cooling machines at Sam Ratulangi University Mechanical Engineering Laboratory, using temperature data from refrigerant R-600a as well as electrical current data. The observational values of the data were obtained by three prominent data, each experiment was conducted for 90 minutes on refrigerant variations.The results of observation of data for the average temperature decrease, which can reach a temperature of 4.1 ° C.  The relationship between coldbox temperature and time. R-600a refrigerant has an average temperature drop of 0.0398 °C/s. And the rate of cooling to electricity consumption when the cooling machine began to operate increased where at the starting point of 1.04 A with a temperature of 28 ° C, to the end point of 1.3 A With a temperature of 4.1 ° C the average increase in electricity consumption was 0.0038 A / s.